The Use of Webpage in English Teaching - Ananda Taqwa; Florence Evelin Masumbauw; Fika Widya Christy Hoogendyk (Magister Kajian Bahasa Inggris (English Language Studies) Universitas Sanata Dharma Yogy, 2019)
There has been a change in the realm of education these days. Started with teachers as the center of learning back then, becoming students as the main key of learning, and this has led to an independent learning environment. Technology has been taking an important role of this change happening in the society, with no exception in the language education as well. Moreover, it is the fact that in English language, students are required to master four skills, namely speaking, listening, reading, and writing. There have been many ways of teaching those four skills to students, but unfortunately often those strategies do not meet students’ needs. Technology development, therefore, comes to provide new solutions to these issues that both teachers and students could grab the benefits of it. Thereupon in this paper, the authors try to provide insights as comprehensive as possible regarding with technology development, which is webpage, which can be used by teachers to assist the English teaching, especially in the sense of teaching reading and listening skills to students.